Suitable Strangers : The Hungarian Revolution, a Hunger Strike, and Ireland's First Refugee Camp - Sheridan, Vera (Book collections on Project MUSE., 2023)
"In 1956, a group of 548 refugees escaping the violence of the Hungarian Revolution arrived on the shores of Ireland. With its own history shaped by waves of emigration to escape war, famine, and religious persecution, Ireland responded by creating its first international refugee settlement. Suitable Strangers reveals the firsthand experiences of the men, women, and children who lived in the Knockalisheen refugee camp near Limerick. For the majority of those living in the camp, Ireland was meant to be a temporary waystation on their ultimate journeys, primarily to Canada, the United States, and Australia. But after almost six months of uncertainty and feeling neglected by the Irish government, the Hungarian refugees began a hunger strike, which garnered national resentment and international headlines. Vera Sheridan explores this revolt and ensuing events by offering a complex and nuanced examination of the daily routines, state policies, and international motives that shaped life in the camp. A fascinating read for historians as well as those interested in refugee and migrant studies, Suitable Strangers complicates the Irish diaspora by providing a closer look at the realities of Ireland's Knockalisheen refugee settlement"--